Neonatal inhalatory anesthetic exposure: Reproductive changes in male rats - Arena, A. C. [UNESP]; Pereira, O. C M [UNESP] (Elsevier, 2002)
We investigated the effects of an inhalatory anesthetic (ethyl ether) during the neonatal period of brain sexual differentiation on the later fertility and sexual behavior of male rats. Animals were exposed to ethyl ether immediately after birth. At adulthood, body weight, testes wet weight, and plasma testosterone levels were not affected; however, neonatal exposure to ether showed alterations on male fertility: a decrease in the number of spermatids and spermatozoa, an increase in the transit time of cauda epididymal spermatozoa and a decrease in daily sperm production. An alteration of sexual behavior was also observed: decreased male sexual behavior and appearance of homosexual behavior when the male rats were castrated and pretreated with exogenous estrogen. Probably, the ether delayed or reduced the testosterone peak of the sexual differentiation period, altering the processes of masculinization and defeminization of the hypothalamus. Our results indicate that perinatal exposure to ethyl ether during the critical period of male brain sexual differentiation, acting as endocrine disruptors, has a long-term effect on the fertility and sexual behavior of male rats, suggesting endocrine disruption through incomplete masculinization and defeminization of the central nervous system. © 2002 Elsevier B.V. All rights reserved.
Keywords: Ether; Fertility; Rat; Reproduction; Sexual behavior; Sexual differentiation; Testosterone; estrogen; ether; testosterone; anesthesia; animal experiment; animal tissue; body weight; brain sexual differentiation; castration; central nervous system; controlled study; epididymis tail; estrogen therapy; exposure; female; fetus; homosexuality; hypothalamus; male; male fertility; newborn; nonhuman; priority journal; rat; reproduction; sex differentiation; sexual behavior; spermatid; spermatogenesis; spermatozoon; testis weight; testosterone blood level; Anesthetics, Inhalation; Animals; Animals, Newborn; Ether, Ethyl; Female; Infertility, Male; Male; Pregnancy; Rats; Sexual Behavior, Animal; Animalia